A descriptive study of feline mandibular fractures presenting to two dental referral practices in South Africa and Canada - Steenkamp, Gerhardus (University of Pretoria, 2023)
Dissertation (MSc (Section Diagnostic Imaging))--University of Pretoria, 2022.